Redescription of two Ctenidae (Araneae) from Taiwan - Marusik, Yuri M.; Omelko, Mikhail M. (Zootaxa, 2016)
Two ctenid species, Anahita maolan Zhu, Chen & Song, 1999 and Ctenus yaeyamensis Yoshida, 1998 from Taiwan are redescribed in detail based on both sexes. Anahita maolan is reported from Taiwan for the first time. For both species, Kenting National Park (southernmost Taiwan) is the southernmost known locality.